Exploring parental opinions on oral hygiene behavior and knowledge of their young children in Lithuania: a cross-sectional survey study - Buunk-Werkhoven, Yvonne A. B.; Tamulienė, Rasa; Mačiulienė, Daiva (Frontiers in Oral Health, 2025)
BackgroundAn appropriately formulated oral health education program carefully based on research, can increase knowledge, change behavior in a positive direction and improve self-confidence. This study aimed to examine parental opinions on their children's oral hygiene behavior (OHB) and oral health knowledge (OHK) among their pre- and primary school children in Kaunas, Lithuania.MethodsIn this cross-sectional study, an online 33-question survey was conducted before and after World Oral Health Day on March 20 to assess the oral hygiene skills, eating habits, and demographics of their 5–12 year children. A total of 532 parents participated, with data from 420 parents, mainly married mothers (average age 37.3 years) being analyzed. Most participants had higher education, lived in Kaunas, and had one to three children, with an average age of 7 years for the oldest child.ResultsMost participants used a manual toothbrush. The adapted OHB index showed that most parents generally had good control over their children's tooth brushing habits, with many brushing twice daily and using fluoride toothpaste. One-third of parents always re-brushed their child's teeth after the child brushed independently. Parents demonstrated strong knowledge of their children's oral health care, as reflected in high scores on the adapted OHK index. A positive correlation was found between OHB and OHK (r = 0.14, p = 0.05). Younger children were re-brushed more frequently, and higher parental OHK was linked to more frequent re-brushing, particularly for children less than 10 years, and parents with higher education had better OHK but did not demonstrate better OHB.ConclusionsThe insights gained from parents into their children's OHB and OHK can help implement an evidence-based preventive approach to improve their children's oral hygiene practices.